STUDI KUAT PENAMPANG ABUTMEN BETON BERTULANG DENGAN MUKA PENAMPANG YANG MIRING HORIZONTAL. JALAN TOL PANDAAN – MALANG JAWA TIMUR - Rahmat Hidayatullah; Pujo Priyono; Adhitya Surya Manggala (Universitas Muhammadiyah Jember, 2020)
One important element in the bridge is located on the abutments of the bridge, where the abutments carry the load at the top of the bridge that is planned to use the crosssection of reinforced concrete the field of contact oblique to the horizontal that the results obtained from the safe with the range of variation of slope on cross-section is in particular on the bridge Pandaan-Malang.With different angles of inclination which varies, for a slope of 0 degrees can beconcluded controlled press, while for a slope of 15 degrees can be concludedcontrolled press for a reinforcement ratio of 0.00 and 0.25 while for a reinforcementratio of 0.5 and 0.75 restrained tensile den with a slope of 40 degrees can beconcluded controlled press.For the existing condition of his own who were in the field with a slope of 10 degreesthe reinforcement ratio of 0.75 can be simpilkan controlled pull.